2015
DOI: 10.1111/jpet.12100
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Capital Taxation in a Neoclassical Growth Model

Abstract: This paper studies the optimal factor tax incidence in a neoclassical growth model with a given share of government expenditure in output. In the Ramsey planner's optimization, the effect of next period's capital on government expenditure equals the given share of the marginal product of capital. Capital accumulation reduces the discounted net marginal product of next period's capital by way of increasing government expenditure. In order to internalize the distortion, it is optimal to tax capital income in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In an infinite-horizon endogenous growth model with human-capital formation, Chen and Lu (2013) showed that a positive long-run capital tax is optimal if raw labor and learning-based human capital are inseparable so that they cannot be taxed separately. Lu and Chen (2015) obtained a positive long-run capital tax in the model of Chamley (1986) without human capital when the government expenditure is maintained at a fixed proportion of output so that the social marginal product of capital is below its private counterpart (thus requiring a tax to correct this distortion). Reis (2011) found that capital income taxation is positive when there are two types of labor: production labor and entrepreneurial labor.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In an infinite-horizon endogenous growth model with human-capital formation, Chen and Lu (2013) showed that a positive long-run capital tax is optimal if raw labor and learning-based human capital are inseparable so that they cannot be taxed separately. Lu and Chen (2015) obtained a positive long-run capital tax in the model of Chamley (1986) without human capital when the government expenditure is maintained at a fixed proportion of output so that the social marginal product of capital is below its private counterpart (thus requiring a tax to correct this distortion). Reis (2011) found that capital income taxation is positive when there are two types of labor: production labor and entrepreneurial labor.…”
Section: Related Literaturementioning
confidence: 99%
“…Notice that this wage discount schedule only depends on the market effective capital-labor ratio    . From ( 11), ( 18), (27), and the Keynes-Ramsey relationship governing consumption growth, we can see that for each   , the pre-tax real rental rate   is increasing in the capital tax rate but decreasing in the labor tax rate as long as the labor cost share in the goods sector (1 − ) is sufficiently high:…”
Section: Equilibriummentioning
confidence: 99%
“…The intuition behind these two results regarding the optimal capital tax rate can be explained as follows. First, as pointed out by Lu and Chen (2015), when government spending is a fixed fraction of total output, capital accumulation reduces the discounted net marginal product of capital by increasing its expenditure. It turns out that it is optimal to tax capital income so as to internalize the distortion.…”
Section: Transitional Dynamics Of Optimal Factor Tax Ratesmentioning
confidence: 99%
“…An important question in public finance is whether taxing capital can lead to lower investment and lower capital stock, also affecting the economic growth rate (Kang & Ye, 2019; Lu & Chen, 2015; Piergallini, 2021; Renström & Spataro, 2021; Suzuki, 2021). In this paper we draw on the theoretical apparatus underlying the fundamental equation of capital theory.…”
Section: Introductionmentioning
confidence: 99%